High prevalence of prediabetes and type 2 diabetes, and identification of associated factors, in high-risk adults in Vietnam: A cross-sectional study - Tran Bao Vuong; Triet Minh Tran; Nam Quang Tran (Diabetes Epidemiology and Management)
Objectives: The prevalences of diabetes and prediabetes have increased rapidly in recent years in emerging nations such as Vietnam, particularly in the population at high risk of diabetes. This study aimed to investigate the prevalence of prediabetes and undiagnosed diabetes in individuals at high risk of type 2 diabetes (T2D), as well as the related risk factors. Methods: This cross-sectional study at the clinics of the University Medical Center in Ho Chi Minh City included 360 patients who were 18 years of age or older, and were at risk of developing T2D. The diagnosis of prediabetes and diabetes relied on measurements of fasting plasma glucose, HbA1c, and 2-hour plasma glucose after a 75 g oral glucose tolerance test. Results: The prevalence of prediabetes was 60.6 % (95 % CI: 55.3–65.6 %), and the prevalence of diabetes was 18.3 % (95 % CI: 14.6–22.8 %). Older age (OR = 1.06), obesity (OR = 3.89), hypertension (OR = 5.71), and dyslipidemia (OR = 2.01) were factors associated with increasing frequencies of undiagnosed T2D and prediabetes. Conclusion: The prevalences of prediabetes and undiagnosed diabetes were significantly higher among people with a high-risk of dysglycemia in Vietnam. There is a need for screening programs for such high-risk individuals.